HAEMATOLOGICAL CHANGES IN PREGNANT RATS AND THEIR DESCENDANTS DUE TO TERATOGENIC DOSE OF CADMIUM CHLORIDE - VENKATRAMANA REDDY ARVA TATIREDDIGARI; KALPANA PANATI; VENKATA R.NARALA (The Bioscan, 2012)
The present study was envisaged to evaluate the effect of teratogenic dose of Cadmium Chloride (CdCl2) in pregnant rats as well as their descendants on haematological parameters. Teratogenic dose (15mg of CdCl2/ kg body weight) when given to pregnant rats from day 7 to 15 of gestation has caused a marked elevation in Red blood corpuscles (RBC), Haemoglobin (Hb), packed cell volume (PCV), mean corpuscle haemoglobin concentration (MCHC) and white blood corpuscles (WBC) on day 15 and 20 of gestation period. In contrast we noticed a fall in mean corpuscle volume (MCV) and mean corpuscle haemoglobin (MCH) in dams treated with teratogenic dose of CdCl2. The changes were more prominent on 20th day when compared to 15th day pregnant rats. However no significant change was noticed in the offsprings from these dams, when their blood was checked for the same parameters on day 10th and 30th of their postnatal age. Thus, results of the present study revealed that haematological parameters of maternal blood are quite susceptible to teratogenic dose of CdCl2 than to produce alterations in their offsprings.